(untitled) (IPS Journal of Nutrition and Food Science, 2023)
Oryza sativa (rice) is a widely consumed staple grain with significant amount of fibre, carbohydrate, and trace amount of other biomolecules such as minerals and vitamins. Thus, it’s a good energy source. The pre-clinical and clinical investigations of rice hull has revealed its numerous health benefits. Utilization of rice products as dietary supplements, additives and pharmacological adjuvants has become a global trend. Rice husk (RH), is a by-product of rice milling generated in tremendous quantity. Considering the global trend in codeine consumption especially by the youths, this study adopted codeine as a drug of abuse as against its therapeutic use as an analgesic. The study explored the haematopoietic potential of rice husk methanol extract (RHME) in codeine-administered male Wistar rats. A total of thirty-six (36) rats weighing between 100-110g were procured and assembled into 6 groups of 6 rats. Group I was the negative control (NC), Group II received codeine at 10mg/kg body weight, Group III received 10mg/kg body weight of RHME, while Groups IV, V, and VI received codeine with RHME concurrently but at three different concentrations of 250, 500, and 1000mg/kg respectively. After 30 days of treatment, blood samples of the specimens were subjected to haematological assay. From the assessment, codeine administration significantly decreased the haematological indices (PCV, haemoglobin, RBC, WBC, platelets, neutrophil, eosinophil, lymphocyte and monocyte), while RHME administration significantly upregulated the altered blood parameters concentration. Thus, RH showed haematopoietic efficacy and should be considered a possible therapeutic for prevention and/or management of anaemia as well as boosting of key haematology indices.